Dad - Root, Betty (Collins publishers ltd, 1991)
Dads can do everything. They help you with your homework, fix things around the house, and teach you how to ride a bike. Dads are the source of all wisdom in the world, which is why you should absolutely not get him that boring tie again for Father$1 (Bs Day! From notorious authors, comedians, U.S. presidents, and even dads themselves, this little book is jam-packed with sensible and laugh-out-loud quotes that are sure to capture just the way you feel about Dad this Father$1 (Bs Day.s
Keywords: Juvenile literature-Fiction